A Chronic Scheme of Cranial Window Preparation to Study Pial Vascular Reactivity in Murine Cerebral Malaria. (11th July 2013) - Ong, Peng Kai; Meays, Diana; Frangos, John A.; Carvalho, Leonardo J.M.
Abstract Objective The acute implantation of a cranial window for studying cerebroarteriolar reactivity in living animals involves a highly surgically invasive craniotomy procedure at the time of experimentation, which limits its application in severely ill animals such as in the experimental murine model of cerebral malaria (ECM). To overcome this problem, a chronic window implantation scheme was designed and implemented. Methods A partial craniotomy is first performed by creating a skull bone flap in the healthy mice, which are then left to recover for one to two weeks, followed by infection to induce ECM. Uninfected animals are utilized as control. When cranial superfusion is needed, the bone flap is retracted and window implantation completed by assembling a perfusion chamber for compound delivery to the exposed brain surface. The presurgical step is intended to minimize surgical trauma on the day of experimentation. Results Chronic preparations in uninfected mice exhibited remarkably improved stability over acute ones by significantly reducing periarteriolar tissue damage and enhancing cerebroarteriolar dilator responses. The chronic scheme was successfully implemented in ECM mice, which unveiled novel preliminary insights into impaired cerebroarteriolar reactivity and eNOS dysfunction. Conclusion The chronic scheme presents an innovative approach for advancing our mechanistic understanding on cerebrovascular dysfunction in ECM.